The Effect of Good Management Planning on The Performance of Employees of Al-Imam General Hospital - Alotaibi, Abdan Shaher; Sumaida, Omar Ali Al-Sagheer (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to identify the impact of good administrative planning on the performance of health sector workers. A field study on employees of Al-Eman General Hospital in Riyadh, and the study followed the descriptive analytical approach. The study population consisted of employees in Al-Eman General Hospital in Riyadh, and the sample size reached 63 employees in Al-Eman General Hospital in Riyadh Where the questionnaire was relied upon as a data collection tool, and the SPSS statistical analysis program was used to analyze the study data. The study reached a number of results, the most important of which are: The workforce planning has an impact on the job performance of the employees of Al-Iman Hospital, and it is largely applied and based on the results, that there is a statistically significant relationship between the practice of continuous workforce planning and job performance, as well as the absence of a significant effect in the workforce planning practice. Likewise, manpower planning is an appropriate way to track performance, but it is not sufficient, and this necessitates the need for control to be seen as entering the institution’s work and role. In light of this, the study recommends the following: - The imperative of a planning system by the management of the institution that corresponds to the aspirations of the institution in the first place, and contributes even a little to raising and improving the level of performance it has. - Forming specialized committees entrusted with the task of designing the planning structure, its regulations, procedures, supervising its implementation and making it understandable and clear by the institution. - Using planning methods and approaches that contribute to assessing performance in every objectivity and do not cause embarrassment to the institution.